2004
DOI: 10.1073/pnas.0402433101
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional imaging of 3D microfluidic mixers using optical coherence tomography

Abstract: To achieve high mixing efficiency in microfluidic devices, complex designs are often required. Microfluidic devices have been evaluated with light and confocal microscopy, but fluid-flow characteristics at different depths are difficult to separate from the en face images produced. By using optical coherence tomography (OCT), an imaging modality capable of imaging 3D microstructures at micrometer-scale resolutions over millimeter-size scales, we obtained 3D dynamic functional and structural data for three repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…This study showed that mixing through diffusion is efficient for stop-flow reactions in microfluidic devices. In a related study, we characterized mixing patterns in more complex microfluidic devices designed for enhancing mixing under continuous flow conditions (Xi et al, 2004).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that mixing through diffusion is efficient for stop-flow reactions in microfluidic devices. In a related study, we characterized mixing patterns in more complex microfluidic devices designed for enhancing mixing under continuous flow conditions (Xi et al, 2004).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Although the fabrication and use of microfluidic devices has been highly successful, the understanding of flow phenomena and biochemical reaction kinetics in these systems is still limited because of the lack of appropriate analysis tools. In the past, several methods have been used to characterize flow phenomena in microfluidic devices including light microscopy (Therriault et al, 2003), confocal microscopy (Liu et al, 2000;Stroock et al, 2002), laser particle velocimetry (Grant, 1997;Meinhart et al, 1999), fluorescence correlation spectroscopy (Brinkmeier et al, 1999;Dittrich and Schwille, 2002) and optical coherence tomography (Schaefer et al, 2004;Xi et al, 2004). However, few studies have investigated real-time biochemical reaction kinetics in microfluidic devices (Kamholz et al, 1999;Liu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…So usually OCT is not used to obtain images of the samples in the microfluidic channel. Instead, it can be used to measure the flow velocity of the fluid in microfluidic channels [34][35][36][37][38][39] A typical setup for a Doppler OCT system 38 is shown in Fig. 1(a), where the spectral domain OCT is used.…”
Section: Bulky Optical Imaging Techniquesmentioning
confidence: 99%
“…3D-image reconstruction is a promising means to interpret a flow field exactly, so avoiding poor estimates. These techniques include magnetic-resonance imaging ͑MRI͒, 25 nuclear-magneticresonance ͑NMR͒ microscopy, [26][27][28] circular-dichroism spectra with synchrotron radiation ͑CDSR͒, 29 and optical-coherence tomography ͑OCT͒, 30,31 and the use of a deconvolution microscope, 32 laser-sheet illumination microscope, 33 confocal microscope, 34 two-photon absorption fluorescence microscope, 35 and a coherent anti-Stokes Raman scattering ͑CARS͒ microscope. 36 They have received much attention in the biological and medical fields, and their application to microfluidics is thriving.…”
Section: Introductionmentioning
confidence: 99%